New Link in Bioinformatics Services Value Chain: Position, Organization and Business Model - Mladen Čudanov; Gheorghe Săvoiu; Ondrej Jaško (Amfiteatru Economic)
This paper presents development in the bioinformatics services industry value chain, based on cloud computing paradigm. As genome sequencing costs per Megabase exponentially drop, industry needs to adopt. Paper has two parts: theoretical analysis and practical example of Seven Bridges Genomics Company. We are focused on explaining organizational, business and financial aspects of new business model in bioinformatics services, rather than technical side of the problem. In the light of that we present twofold business model fit for core bioinformatics research and Information and Communication Technologie (ICT) support in the new environment, with higher level of capital utilization and better resistance to business risks.